Odpowiedzi

2009-11-23T20:31:28+01:00
- sześć i dwie trzecie = jeden i jedna trzecia

równanie sprzeczne.
Najlepsza Odpowiedź!
2009-11-23T20:33:41+01:00
X/3x-7=3x-7/9x
Zakładam, że jest tak:
x/(3x - 7) = (3x-7)/(9x)
Musimy wykluczyć x, dla których mianownik jest równy 0
9x ≠ 0 i 3x - 7 ≠ 0
x ≠ 0 i 3x ≠ 7 |:3
x ≠ 7/3

x/(3x - 7) = (3x-7)/(9x)
(3x - 7) × (3x-7) = x × 9x
9x² - 42x + 49 = 9x²
-42x = -49 |: (-42)
x = 49/42
x = 7/6
2009-11-23T20:34:45+01:00
X/3x-7=3x-7/9x /*3x
x-7=3x-7/3
x-3x=7-7/3
2x=4⅔ /:2
x = 9⅓